2016
DOI: 10.3390/en9121058
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeability Rates of Vanadium Ions and Their Effects on Temperature Variation in Vanadium Redox Batteries

Abstract: Abstract:The inevitable diffusion of vanadium ions across the membrane can cause considerable capacity loss and temperature increase in vanadium redox flow batteries (VRFBs) over long term operation. Reliable experimental data of the permeability rates of vanadium ions are needed for membrane selection and for use in mathematical models to predict long-term behavior. In this paper a number of ion exchange membranes were selected for detailed evaluation using a modified approach to obtain more accurate permeati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…Choi et al also evaluated three commercial AEMs—Selemion APS, AHA and AFN—as separators in VRFBs [ 28 ]. More recently, the possibility of commercial Fumasep AEMs for VRFB application has also been examined by several research groups [ 29 , 30 , 31 ]. Cao et al [ 29 ] evaluated the permeation rate of the different vanadium ions across Fumasep ® FAP-450 with a comparison to N115, and Nguyen’s group [ 30 ] examined FAP-450 with respect to vanadium ion uptake under both static equilibria and after cell operating conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al also evaluated three commercial AEMs—Selemion APS, AHA and AFN—as separators in VRFBs [ 28 ]. More recently, the possibility of commercial Fumasep AEMs for VRFB application has also been examined by several research groups [ 29 , 30 , 31 ]. Cao et al [ 29 ] evaluated the permeation rate of the different vanadium ions across Fumasep ® FAP-450 with a comparison to N115, and Nguyen’s group [ 30 ] examined FAP-450 with respect to vanadium ion uptake under both static equilibria and after cell operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the possibility of commercial Fumasep AEMs for VRFB application has also been examined by several research groups [ 29 , 30 , 31 ]. Cao et al [ 29 ] evaluated the permeation rate of the different vanadium ions across Fumasep ® FAP-450 with a comparison to N115, and Nguyen’s group [ 30 ] examined FAP-450 with respect to vanadium ion uptake under both static equilibria and after cell operating conditions. Besides ion exchange membranes (IEMs), non-ionic porous membranes have also been tried for VRFB such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polybenzimidazole (PBI) and polyvinylpyrrolidone (PVP)-based porous membranes due to their excellent mechanical stability, high chemical resistance and low cost [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The serpentine–parallel pattern of the stack flow channel was recommended for uniform flow of the electrolyte. The membrane permeability rates of vanadium ions with temperature variation were discussed by Cao et al [ 118 ] Yan et al [ 41 ] discussed the effects of battery design, environmental temperature, and electrolyte flow rate on the thermal behavior of VRFBs in different applications. It was found that the temperature rise inside the VRFB stack may exceed its safe limit at higher charging and discharging currents.…”
Section: Modeling Of Vrfbmentioning
confidence: 99%
“…The two types of membrane were found to behavev ery differently, with the AEM showingvery high selectivity for V V ,which resulted in as ignificant increase in area-specific resistivity.I nc ontrast, the CEM absorbed V II more strongly than vanadium in other oxidation states. [13] Besides that, the study by Yang et al also examined the effects of the electric fieldo nt he ion crossover in VRFBs. to precipitation below 10 8Ca nd above 40 8C).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that AEMs have lower vanadium permeability than CEMs, which resultsf rom the Donnan exclusion effect:r epulsion of cations from the positively chargedf unctional groups in the membrane. [12] However,a study by Sun [13] Besides that, the study by Yang et al also examined the effects of the electric fieldo nt he ion crossover in VRFBs. [14] In general,u nder operating conditions, vanadium diffusion through IEMs may not only be determined by the electrostatic interaction of membrane-electrolyte species, but may also be influencedb yo ther factors, such as electrolyte flow rates, electric field gradient, and differential pressure.…”
Section: Introductionmentioning
confidence: 99%